(untitled) (Experimental biology, 2015)
In the during the experiment in laboratory conditions was revealed the effect of different concentrations of heavymetals on the anatomical and morphological structure of maize (Zea Mays L.). Experiments were performed in triplicate and in four variants. In 3 variants were added different concentrations of CuSO4 and 4- variant was studied as a control. Influence of heavy metals on growth and development of maize (Zea Mays L.) was observed. During the research it was found that increasing concentrations of heavy metals leads to restriction of growth and development of maize. A comparative analysis of morphometric parameters of maize grown in laboratory and field conditions was determined. It was proved that heavy metals affect the anatomical structure of the leaves and roots of maize.